The Economic Situation of First- and Second-Generation Immigrants in France, Germany, and the UK - Yann Algan; Christian Dustmann; Albrecht Glitz; Alan Manning (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2009)
A central concern about immigration is the integration into the labour market, not only of the first generation, but also of subsequent generations. Little comparative work exists for Europe's largest economies. France, Germany and the UK have all become, perhaps unwittingly, countries with large immigrant populations albeit with very different ethnic compositions. Today, the descendants of these immigrants live and work in their parents' destination countries. This paper presents and discusses comparative evidence on the performance of first- and second-generation immigrants in these countries in terms of education, earnings, and employment.
Keywords: 330